Labor Market "Rigidity" and the Success of Economic Reforms across More than 100 Countries - Forteza, Alvaro (World Bank, Washington, DC, 2014)
The authors show that labor market policies and institutions affect the effectiveness of economic reform programs. They compare annual growth rates across 119 countries, using data from 449 World Bank adjustment credits and loans between 1980 and 1996. The results indicate that countries with relatively rigid labor markets experienced deeper recessions before adjustment and slower recoveries afterward. The results also disentangle the mechanisms through which labor market rigidity operates. They find that minimum wages and mandatory benefits do not hurt growth. But the relative size of organized labor (in government and elsewhere) appears to matter. Labor market rigidity seems to be relevant more for political reasons than for economic reasons. The authors' findings suggest that not enough attention has been paid to vocal groups (urban, middle-class groups) that stand to lose from economic reform. The implications of the findings for policymakers: There should be less focus on deregulating the labor market and more on defusing the opposition of (vocal) losers. The results are robust to changes in measurement, controls, and sample, and do not suffer from self-selection bias.